Refsum's disease: a peroxisomal disorder affecting phytanic acid alpha-oxidation. - Wierzbicki, A; Lloyd, MD; Schofield, C; Feher, MD; Gibberd, F (2002)
Refsum's disease (hereditary motor sensory neuropathy type IV, heredopathia atactica polyneuritiformis) is an autosomal recessive disorder the clinical features of which include retinitis pigmentosa, blindness, anosmia, deafness, sensory neuropathy, ataxia and accumulation of phytanic acid in plasma- and lipid-containing tissues. The transport and biochemical pathways of phytanic acid metabolism have recently been defined with the cloning of two key enzymes, phytanoyl-CoA 2-hydroxylase (PAHX) and 2-hydroxyphytanoyl-CoA lyase, together with the confirmation of their localization in peroxisomes. PAHX, an iron(II) and 2-oxoglutarate-dependent oxygenase is located on chromosome 10p13. Mutant forms of PAHX have been shown to be responsible for some, but not all, cases of Refsum's disease. Certain cases have been shown to be atypical mild variants of rhizomelic chondrodysplasia punctata type 1a. Other atypical cases with low-plasma phytanic acid may be caused by alpha-methylacyl-CoA racemase deficiency. A sterol-carrier protein-2 (SCP-2) knockout mouse model shares a similar clinical phenotype to Refsum's disease, but no mutations in SCP-2 have been described to-date in man. This review describes the clinical, biochemical and metabolic features of Refsum's disease and shows how the biochemistry of the alpha-oxidation pathway may be linked to the regulation of metabolic pathways controlled by isoprenoid lipids, involving calcineurin or the peroxisomal proliferator activating alpha-receptor.